Discourses of Race and Rising China - Cheng, Yinghong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book is a critical study of the development of a racialised nationalism in China, exploring its unique characteristics and internal tensions, and connecting it to other forms of global racism. The growth of this discourse is contextualised within the party-state's political agenda to seek legitimacy, in various groups' efforts to carve their demands in a divided national community, and has directly affected identity politics across the global diasporic Chinese community. While there remains considerable debate in both academic literature and popular discussion about how the concept of 'race' is relevant to Chinese expressions of identity, Cheng makes a forceful case for the appropriateness of biological and familial narratives of descent for understanding Chinese nationalism today. Grounded in a strong conceptual framework and substantiated with rich materials, Discourses of Race and Rising China will be an important contribution to international studies of racism, and will appeal to academics and students of contemporary China, historians of modern China, and those who work in the fields of critical race, ethnicity, and cultural studies. .
Chapter 1. "Call a Spade a Spade" -- Chapter 2. Two Blacks and One Yellow: Race in Pop Music -- Chapter 3. Is Peking Man Still Our Ancestor?-Race and National Lineage -- Chapter 4. Discovering China in Africa: Race and Sino-African Relations -- Chapter 5. Racism and Its Agents in China -- Chapter 6. The "Red DNA": How Discourses of Class and Race Integrate.
Keywords: Race; China -- History; Race and Ethnicity Studies; History of China